The effect of steel fiber aspect-ratio and content on the fresh, flexural, and mechanical performance of concrete made with recycled fine aggregate - Benli, Ahmet; Shi, Jinyan; Yavuz Bayraktar, Oguzhan; Turkoglu, Mesut; Bodur, Burak; Kaplan, Gökhan (Elsevier BV, 2023)
© 2023 Elsevier LtdIn order to solve the problem of low toughness and easy cracking of recycled aggregate concrete, steel fibers were incorporated to recycled fine aggregate concrete (RAC) to prepare a sustainable fiber-reinforced concrete. Steel fibers of various contents (20, 35, 50 and 65 kg/m3) and aspect ratios (l/d = 40 and 55) were incorporated to the RAC, and their fresh properties, mechanical properties and microstructure were investigated. The results show that the slump of RAC decreases with increasing fiber aspect ratio and content. Meanwhile, incorporating a small amount of steel fibers (l/d = 40, 20 kg/m3) improves the 28-d compressive strength of RAC, but with further increase in fiber aspect ratio and content, the compressive strength of RAC decreases. The incorporation of steel fibers greatly improves the splitting tensile strength and flexural strength of RAC, and the steel fibers with high aspect ratio have a higher gain in strength. The 28-d flexural strength of concrete with 65 kg/m3 steel fibers (l/d = 40) increases by 148.11 % relative to plain RAC, while the 65 kg/m3 steel fibers with an aspect ratio of 55 makes RAC with increases by 243.78 %. The mass loss of fiber-reinforced RAC under abrasion is also lower than that of plain RAC, and the steel fiber with high aspect ratio performs better. For the load–deflection response, the incorporation of fibers increases the peak load, and also increases the flexural toughness and post-cracking toughness, with the greatest gain for high aspect ratio fibers.